ANEMIA AND NUTRITIONAL STATUS AS DOMINANT FACTOR OF THE EVENT LOW BIRTH WEIGHT IN INDONESIA: A SYSTEMATIC REVIEW - Hutagalung, Lisnawati (LIFE: International Journal of Health and Life-Sciences, 2017)
Background: Low birth weight is one cause of newborn death. Babies with low birth weight tend to have slower cognitive development and risk of death. Report data from the World Health Organization (WHO) in 2014, estimates that each year there are 20 million babies have low birth weight of all births in the world. Based on data from the Health Research Association from Health Department of Indonesia in 2013, showed the percentage of low birth weight in Indonesia according to the child’s age (0-59 months) amounted to 10.2% in 2013. Objective: Identify risk factors and dominant factors that influence the incidence of low birth weight in some areas in Indonesia with approach systematic review. Method: This research used some database of public health such as Google Scholar, UGM journals, UI journals and UNAND journals in 2012-2015 with amounts 2084 journals. Data were filtered using keywords "Risk Factors" AND "Cause low birth weight" with amounts 56 study. The filtrate obtained 5 public health researches that meet the criteria. Results: Risk factors associated with low birth weight, among other environment factors (exposure to cigarette smoke and residence), social demographics (age and socio-economic) and maternal factors (anemia, placental abnormal, nutritional status of mothers, examinations antenatal, preeclampsia, parity and complications in pregnancy). Anemia and nutritional status becomes the dominant factor affecting low birth weight. Conclusions: The risk factors that affect low birth weight, most commonly found in the maternal factors. The dominant factors are big effect on low birth weight is anemia and nutritional status of the mother during pregnancy.